Differential lung function in an infant with the Swyer-James syndrome. Issue 4 (April 1989) - Avital, A; Shulman, D L; Bar-Yishay, E; Noviski, N; Schachter, J; Krausz, Y; Godfrey, S
Abstract : A previously healthy two year old boy had an adenoviral infection at the age of 13 months and developed hyperlucency of the left lung, chronic respiratory distress, and failure to thrive. Bronchodilators and steroid treatment had no effect. Radionuclide lung scans using an intravenous bolus of xenon-133 both before and after treatment showed substantially reduced function on the hyperlucent side and modestly reduced function on the other side. Fibreoptic bronchoscopy showed no structural abnormalities. Partial forced expiratory flow volume (PEFV) curves, generated from end inspiration by rapid compression of the chest wall with an inflatable jacket, were obtained from the total respiratory system and from each lung separately by inflating a Fogarty catheter in the contralateral mainstem bronchus. Expiratory flow rates and volumes during both tidal breathing and PEFV manoeuvres were considerably decreased in the hyperlucent lung. PEFV curves from the "healthy" right lung and from the total respiratory system were similar in shape and showed a moderately obstructive pattern. The right lung ventilated about four times as much as the left when measured by bronchospirometry and about three times as much when measured by the radionuclide technique. The lung scans appeared to reflect adequately the functional abnormality in this infant with the Swyer-James syndrome.